2016
DOI: 10.1002/biof.1321
|View full text |Cite
|
Sign up to set email alerts
|

Serum nitrite and nitrate levels, NOx, can predict cardiovascular mortality in the elderly in a 3‐year follow‐up study

Abstract: Nitric oxide (NO) is an important functional regulator that contributes to progression of various cardiovascular diseases. We studied associations between nitric oxide metabolites, nitrite and nitrate (NOx), and cardiovascular mortality in a prospective 3-year follow-up cohort study in 1,869 elderly patients aged over 55 years. The Cox proportional hazard regression model was adjusted for multiple factors including sex, age, risk corresponding to preexisting cardiovascular conditions, and serum inflammatory ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
(28 reference statements)
7
18
0
4
Order By: Relevance
“…Our previous work demonstrated that high concentrations of serum NOx can be considered an independent risk factor associated with increased cardiovascular mortality during 3‐year follow‐up. Some other factors were associated with cardiovascular mortality including age, sex, HDL cholesterol, C‐reactive protein, interleukin‐6, fibrinogen and history of previous cardiovascular events . It should be noted that a number of factors were not associated with mortality in the present study in agreement with our previous results .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Our previous work demonstrated that high concentrations of serum NOx can be considered an independent risk factor associated with increased cardiovascular mortality during 3‐year follow‐up. Some other factors were associated with cardiovascular mortality including age, sex, HDL cholesterol, C‐reactive protein, interleukin‐6, fibrinogen and history of previous cardiovascular events . It should be noted that a number of factors were not associated with mortality in the present study in agreement with our previous results .…”
Section: Resultssupporting
confidence: 92%
“…Mean NOx concentrations were 58.0 ± 30.4 µmol/L. NOx concentrations did not differ between men and women and between subjects of various age groups …”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations